BEHAVIORAL ANALYSIS OF AGRIBUSINESS MANAGEMENT LAYING CHICKEN BREEDERS IN DISTRICT LIMA PULUH KOTA - Rahmi Rizqha (Menara Ilmu, 2017)
This study aims to analyze the behavior of agribusiness management laying chicken breeders in the District Lima Puluh Kota. This research was conducted in Payakumbuhin the district Lima Puluh Kota , for two (2) semester or one academic year. This research is a survey research by making farmers as a source of primary (main data). In this study used two types of data are primary data obtained directly from the respondents and secondary data obtained from government agencies or institutions. The primary data is collected based on the four aspects of the behavior of agribusiness management include: What concrete actions do farmers in business planning, How real action undertaken farmers in the use of environmental resources, How do action / orientation breeders to excellence quality to meet the needs of consumers, How orientation farmers in meeting the needs / market demands. The results showed that, on average behavior of farmers in this area based on four aspects of management that are in high and medium category. None of the farmers who are in the low category. To conduct the overall agribusiness management, the majority of farmers are in a high category, 56.67% and the remaining 43.33% are in the moderate category. This suggests that farmers in this region always apply the principles of agribusiness management in their livestock business. Key words: behavioral breeders, agribusiness management, laying hens